1990
DOI: 10.1200/jco.1990.8.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, immunogenicity, and tumor radioimmunodetecting ability of two human monoclonal antibodies in patients with metastatic colorectal carcinoma.

Abstract: Two human immunoglobulin M (IgM) monoclonal antibodies (MoAbs), 16.88 and 28A32, which react with cytoplasmic (28A32 and 16.88) or cell surface (28A32) determinants on human colon carcinoma cells, were administered intravenously to 26 patients with metastatic colorectal carcinoma to determine if they could localize to sites of metastatic disease, if they had any antitumor or toxic effects, and to determine whether they would elicit an antihuman MoAb response. Serial scans showed tumor uptake of radioisotope in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Potential disadvantages in using IgM mAb include the increased difficulty in purifying an IgM mAb compared to an IgG mAb and the theoretical problem that the large IgM mAb may have difficulty diffusing into extravascular areas. This latter issue has been examined in two recent imaging trials with radiolabeled human IgM mAb; positive tumor localization in patients with solid tumors was demonstrated [20,23]. There have been no reported clinical trials of mouse IgM in vivo for B cell neoplasms, but treatment of involved bone marrow ex vivo with cytotoxic murine IgM mAb and human complement can selectively lyse tumor cells without negatively affecting growth of normal bone marrow progenitor cells [22,24].…”
Section: Discussionmentioning
confidence: 94%
“…Potential disadvantages in using IgM mAb include the increased difficulty in purifying an IgM mAb compared to an IgG mAb and the theoretical problem that the large IgM mAb may have difficulty diffusing into extravascular areas. This latter issue has been examined in two recent imaging trials with radiolabeled human IgM mAb; positive tumor localization in patients with solid tumors was demonstrated [20,23]. There have been no reported clinical trials of mouse IgM in vivo for B cell neoplasms, but treatment of involved bone marrow ex vivo with cytotoxic murine IgM mAb and human complement can selectively lyse tumor cells without negatively affecting growth of normal bone marrow progenitor cells [22,24].…”
Section: Discussionmentioning
confidence: 94%
“…Recognition of the human antibody by the murine immune system and differences in the glycosylation of human and murine Ig may be factors leading to faster catabolism of the human IgM and accumulation of antibody and 125I in the liver. Human monoclonal IgM, with a whole-body half-life of 51 h and a plasma half-life of 26 h in patients, does seem to be cleared more slowly in the autologous organism than in mice (Steis et al 1990). The clearance rates of the monomeric and half-monomeric fragment in patient are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Different dehalogenation rates are found in different tissues, from nearly no dehalogenation in the blood to a high dehalogenation rate in the liver (Halpern et al 1988). Although McCabe et al (1988) found a rather low concentration of ~25I in the xenografted colon tumour, they were still able to detect 58% of colon tumour lesions larger than 2 cm in diameter in colon cancer patients (Steis et al 1990). The lower absolute uptake/retention of half-monomeric COU-1 compared to intact and monomeric COU-1 may affect clinical imaging; however, the faster clearance and early favourable tumour-to-normal tissue ratio may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this possibility has to be monitored always, when murine antibodies are administered. In order to overcome xenogeneic mAb immunogenicity, human or humanised (chimeric or CDRgrafted) mAbs [41][42][43] and more recently their respective Fab) and Fv fragments [44,45] have entered diagnostic or therapeutic pilot preclinical/clinical studies. A CDRgrafted human mAb, Hu2PLAP, against PLAP was constructed by incorporating the CDRs from the murine IgG1 antibody H17E2 into a human IgG1 framework.…”
Section: Discussionmentioning
confidence: 99%